Blepharo-Cheilo-Dontic (BCD) syndrome: Report on four new patients - Guion-Almeida, M. L.; Rodini, E. S.O. [UNESP]; Kokitsu-Nakata, N. M.; Bologna-Amantini, D. (My University, 1998)
We report on four Brazilian patients with, among other signs, cleft lip and palate, dental anomalies, ectropion of the lower eyelids, euryblepharon, and lagophthalmia. Two were sporadic cases and two were familial cases, a mother and her equally affected son. Recently, the reports with different combination of these signs were reviewed by Gorlin et al. [1996; Am J Med Genet 65:109-112] and named blepharocheilo-dontic (BCD) syndrome. Variable expressivity and autosomal dominant inheritance were observed. © 1998 Wiley-Liss, Inc.
Keywords: Ankyloblepharon; Dental anomaly; Ectropion; Euryblepharon; Facial clefting; Lagophthalmia